Enhancing Production: Effects of Royalactin on Insect Development - Piana, Mattia (2022)
Phenotypic plasticity is a phenomenon found in eusocial insects that produces distinct female castes through phenotypic responses to environmental change. Honey bees (Apis mellifera) are a perfect model to study phenotypic plasticity. Worker bees and queen bees, both of which are females, have different adult phenotypes, depending on the diet the larvae are fed during development. Contained within this diet, known as royal jelly, is a protein called ‘Royalactin’. An earlier study showed that Royalactin can induce a queen-like phenotype in female bee larvae and promotes growth and life-span in other species, such as the fruit fly D. melanogaster and the nematode C. elegans. An initial aim of this study was to produce Royalactin in an E. coli expression system and then test its potential growth effects in a set of insects of economic importance. The recombinant protein was produced using an E. coli expression system and confirmed by amino acid sequencing. This thesis describes alternative methods to obtain body-enlarging effects in insects. DNA-methylation inhibitors were used to increase body weight, which prompted the use of RNA interference to study in detail what genes are involved in body growth during development.